Legal Analysis of the Monopoly of Road Construction Service Tenders: A Study of Ternate District Court Decision Number: 8/Pdt.Sus-KPPU/2021/PN.Tte - Astari, Wina; Pakpahan, Elvira Fitriyani; Mulyadi, Mulyadi; Isnainul, OK. (IJBLE Scientific Publications Community Inc., 2025)
The procurement of goods and services in Indonesia must comply with the fundamental principles and legal provisions stipulated in existing laws and regulations. One significant aspect of such procurement involves tenders for public infrastructure projects, including road construction. The tender process must be conducted fairly, transparently, and in accordance with the law. Any form of collusion during the tender process indicates monopolistic practices that can lead to legal consequences and sanctions imposed by the Business Competition Supervisory Commission (Komisi Pengawas Persaingan Usaha—KPPU). This study examines the Ternate District Court Decision Number 8/Pdt.Sus-KPPU/2021/PN.Tte, in which PT. IBS and PT. HNG filed an objection against KPPU Decision Number 30/KPPU-L/2019. The KPPU had imposed administrative sanctions, including fines and a one-year ban from participating in procurement tenders. The objective of this research is to analyze the legal accountability of business actors engaging in monopolistic practices in road construction tenders and to explore the court’s legal reasoning in reviewing the KPPU decision. Using a normative juridical research method with a statutory and descriptive approach, this study relies on secondary data obtained from primary, secondary, and tertiary legal materials. Data were analyzed qualitatively through document and literature review. The findings indicate that business actors proven to engage in tender monopolization may face three forms of legal liability: administrative sanctions, criminal fines ranging from one to twenty-five billion rupiahs, and additional penalties such as license revocation. These measures aim to ensure justice, transparency, and fair competition in Indonesia’s public procurement system.